How do young people interpret the transition undergone on leaving secondary school? Analysing experiences, meanings and expectations. (Praxis Educativa, 2021)
The aim of this paper is to make a qualitative assessment of youthful transitions when finishing secondary school. The main issue addressed by this work revolves around the way in which the young undergo this process while attending their last year of secondary education. The analysis was performed by considering the youth collective’s experiences and post-secondary expectations, which are largely connected with their unique vision in relation to the future they discern for themselves in local scenarios. An in-depth survey was conducted among a purposive sample of young people that attended state-run secondary schools during the 2016-2017 school years. The interviews enquired into the assessment, meanings, feelings, wishes and mandates that characterise this turning point. The findings of the study were then classified into four encompassing categories: educational, socioeconomic, personal, and cultural.